IN HOUSE TRAINING DALAM UPAYA MENJAWAB TANTANGAN GURU MASA DEPAN DI SMA NEGERI 6 HALMAHERA UTARA - Eko Purnomo (Universitas Khairun, 2019)
The profession that is always required to be creative, always innovating is one of the teachers. Current and future teacher professions are very heavy because not only academic competencies such as mastery of subject matter, expertise in designing, managing and evaluating learning with a variety of the latest methods, and skilled in using teaching aids and learning media; but also he must have the maturity and persistence of personality. Teacher professional improvement itself can actually be pursued through a number of ways, namely further study, inhouse training; Empowering subject teachers' deliberations (MGMP), empowering professional organizations, evaluating classroom performance, certification and competency tests. In addition, to take part in the rapid development of science and technology, there are a number of other competencies that teachers must have in the future. These competencies are lifelong learning, science and technology eruption, mastering English, skilled in carrying out classroom action research, communicating scientifically, being able to use and access information technology systems. Keywords: competence, in house training, future teacher challenges